Analisis Kemampuan Pemahaman Konsep Siswa Kelas VIII SMP pada Materi Lingkaran - Yufentya, W Eggy; Roza, Yenita; Maimunah, Maimunah (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to describe the ability to understand students' concepts for each indicator so that it is known on which indicators students experience problems. The method used in this study is descriptive qualitative. Based on the results of data analysis, it can be concluded that high-ability students have the ability to understand good concepts because they have reached more than 50% for each indicator. While for students with moderate and low ability, they have a poor understanding of the concept because the results obtained are less than 50% for each indicator.